The Influence Of Organizational Environment, Commitment, Leadership And Job Satisfaction On Turnover Intention at PT. X - Dwi Puspita Firdaus (Universitas Syiah Kuala, 2023)
Management of human resources (HR) by the company needs to be done to avoid turnover intention or the desire to move that arises from employees. This study aims to determine the relationship and influence of organizational environment, organizational commitment, leadership, and job satisfaction on employee turnover intention at PT. X. The research was conducted by giving questionnaires to the entire population of 37 employees of PT. X. Statistical analysis used is Multiple Linear Regression Analysis which allows to determine the relationship and the magnitude of the influence between variables. The results of the study at a significance level of 5% indicate that the organizational environment, organizational commitment, leadership, and job satisfaction have a negative and significant effect on employee turnover intention at PT. X either simultaneously, or partially. The independent variable can explain the dependent variable (turnover intention) of 70.1% and the remaining 29.9% are other factors that can affect employee turnover intention.